Distribution of serotonin (5-HT) and dopamine (DA) on digestive tract of red palm weevil larva, Rhynchophorus ferrugineus (Coleoptera: Dryophthoridae) - Harris M.N.,; Norefrina Shafinaz Md Nor,; S. Yaakop,; Nurul Wahida Othman, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The red palm weevil (RPW), Rhynchophorus ferrugineus (Coleoptera: Dryopthoridae) is a well-known deadly pest of palmae tree worldwide. The larvae of RPW is the most destructive stage of its life cycle and caused great economic lost to palm tree plantation for example the coconut tree plantations. In this study, we focused on detection of two important biogenic amines, serotonin (5-HT) and dopamine (DA) that play important roles in the regulation of the digestive tract of this insect. Immunohistochemistry analysis has been carried out on the cross-sectioned tissue of three different parts of the digestive tract; foregut, midgut and hindgut. 5-HT receptor for serotonin and D1 receptor for dopamine were chosen for chromogenic detection of the biogenic amine. The distribution of 5-HT can be detected at the plasma membrane, basement membrane and cytoplasm of the cell for the whole guts except at the midgut cell. While DA can only be detected at the basal membrane of the gut cell for the most part of the gut. Further study could be done to find a possible solution in controlling the survival of RPW by understanding the roles of the biogenic amine in controlling and modulating the mechanism of absorption and digestion of the digestive tract.